1982
DOI: 10.1136/vr.111.12.263
|View full text |Cite
|
Sign up to set email alerts
|

Collie eye anomaly in the United Kingdom

Abstract: Approximately 2500 rough collies, smooth collies and Shetland sheepdogs were examined during a three year period in an attempt to establish the incidence of collie eye anomaly in the United Kingdom and to produce data on the hereditability of the disease. The overall incidence in the two collie breeds was approximately 64 per cent, but the disease was seen with slightly more frequency in the Shetland sheepdog, 72 per cent of the dogs examined being affected. Pedigree analysis and test mating has confirmed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 0 publications
1
52
1
Order By: Relevance
“…Intraocular haemorrhage is not common. Bedford (1982b) found it in approximately 1% of dogs with CEA only. It may appear as unclotted blood in the anterior eye chamber or as pre-retinal bleeding and is most likely to result from bleeding from abnormal vessels in the retina.…”
Section: Clinical Signsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intraocular haemorrhage is not common. Bedford (1982b) found it in approximately 1% of dogs with CEA only. It may appear as unclotted blood in the anterior eye chamber or as pre-retinal bleeding and is most likely to result from bleeding from abnormal vessels in the retina.…”
Section: Clinical Signsmentioning
confidence: 99%
“…Thanks to the congenital presence of the disease, early ophthalmoscopic diagnosis is possible. The examination is both practicable and advisable at six weeks of age (Bedford 1982b). A problem in diagnosis is the "go normal" phenomenon.…”
Section: Clinical Signsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic cause of this variability is unknown. Yakely (1972) reported CEA in 70-97% Rough and Smooth Collies in the USA, likewise Bedford (1982a) in Great Britain. Wallin-Hakanson et al (2000) observed CEA in approximately 68% of Rough Collies in Sweden.…”
mentioning
confidence: 99%